2022
DOI: 10.14202/vetworld.2022.2131-2140
|View full text |Cite
|
Sign up to set email alerts
|

Identification of antinutritional, antioxidant, and antimicrobial activity of plants that cause livestock poisoning in Bojonegoro Regency, Indonesia

Abstract: Background and Aim: The utilization of cassava leaves and peels, ceara rubber leaves, sweet potato leaves, Chinese Albizia leaves, and lophatheri leaves from Bojonegoro Regency has led to the poisoning of livestock due to antinutritional factors. Nevertheless, the plants are known to have bioactive components and potential antioxidant and antibacterial activity if appropriately processed. This study aimed to determine the antinutritional compounds as well as the antioxidant and antibacterial potential of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Based on the interpretation criteria used by Odilla, et al (2022), antibacterial potency can be classified into weak (diameter <12 mm), moderate (diameter 12-20 mm), and strong (diameter 20 mm). 32 Abiding by this classification, all of the extract concentrations displayed weak antibiotic properties against both MSSA and MRSA, as evidenced by the average diameter of <12 mm.…”
Section: Discussionmentioning
confidence: 85%
“…Based on the interpretation criteria used by Odilla, et al (2022), antibacterial potency can be classified into weak (diameter <12 mm), moderate (diameter 12-20 mm), and strong (diameter 20 mm). 32 Abiding by this classification, all of the extract concentrations displayed weak antibiotic properties against both MSSA and MRSA, as evidenced by the average diameter of <12 mm.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, sweet ethanolic extract of potato leaves containing tannins, alkaloids, and cardiac glycosides inhibits the growth of S. epidermidis, S. aureus and E. coli (<12 mm-bacterial IZ). In that study, the authors noted that cassava leaves ethanolic extract was more effective in antibacterial activity against S. aureus and E. coli than ethanolic extract of cassava peels in 125 and 250 mg/mL concentrations [65].…”
Section: Antimicrobial Activity Toward Microbial Pathogensmentioning
confidence: 92%
“…A study by Ahmed et al (2018) showed that banana peel inhibits the growth of other bacteria, including the growth of S. aureus at 1%, 3%, and 5% with a diameter of inhibition zone of 0.6, 1.5, and 2 mm. The extract of cassava peel (M. esculenta) can inhibit S. aureus, epidermidis, and E. coli (Odilia et al 2022). Still, no information regarding the inhibitory activity against A. hydrophila.…”
Section: Minimum Inhibitory Concentration (Mic) Valuementioning
confidence: 99%
“…The banana peel extract had antibacterial activity against S. aureus and S. pyogenes (Chabuck et al 2013). A study by Odilia et al (2022) showed that the extract of cassava peels was active against S. aureus, S. epidermis, and E. coli, while the extract of pineapple peel was active against S. aureus, E. coli, P. aeruginosa, Vibrio cholerae and K. pneumoniae (Lubaina et al 2019). However, a study on cassava peel and pineapple peel extract as an antibacterial for A. hydrophila is still limited.…”
Section: Introductionmentioning
confidence: 99%